Tantangan dalam Penerapan Teori Behavioristik Berbasis Etnomatematika dalam Meningkatkan Minat Belajar Matematika Siswa Kelas 5 Sekolah Dasar - Yatra, I Ketut Adi Darma; Suarni, Ni Ketut; Margunayasa, I Gede (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the influence of the application of ethnomathematics-based behavioristic theory on interest in learning mathematics in grade 5 elementary school students. This research adopted an experimental research design involving 30 students as a representatively selected sample. Data was collected through observation and interviews to understand changes in students' learning interest before and after the intervention. Data analysis was carried out by combining descriptive and statistical approaches. The research results show that there has been a significant increase in interest in learning mathematics, with an average of 90, compared to only 70 previously. These findings support the effectiveness of ethnomathematics-based behavioristic theory in stimulating students' interest in learning.